Die gebeure en karakters in Eksodus 2 : 'n studie van die storie-aspekte in die narratiewe teks van Eksodus 2 (deel 1) - Brink, Aldert (Old Testament essays, 2002)
A narrative consists of three dimensions, that of story, text and narrator. In this article the author concentrates on two aspects of the story dimension and their interrelation. The two aspects are those of events and characters. Events don't happen in isolation - somebody must make them happen; or - they must happen to somebody. If no characters exist, nothing can happen because there is nobody who can make it happen or to whom it can happen. It is also true that characters cannot exist if they do not do something or if something does not happen to them. Thus, there exists a creative interaction between these two aspects.